Melatonin suppresses serum starvation-induced autophagy of ovarian granulosa cells in premature ovarian insufficiency - Di Wu; Wenjie Zhao; Chengjuan Xu; Xin Zhou; Xia Leng; Yanmin Li (BMC, 2022)
Abstract Objectives Premature ovarian insufficiency (POI) refers to the decline and cessation of ovarian functions in women under 40 years of age. Melatonin (MT) acts as a protective for the ovary. This study elucidated the role of MT in autophagy of granulosa cells (GCs) in POI via modulating the phosphatidylinositol-3-kinase (PI3K)-Akt-mammalian target of rapamycin (mTOR) pathway. Methods The expression levels of microRNA (miR)-15a-5p, signal transducer and activator of transcription 3 (Stat3), and relevant hormones in the clinically collected serum samples of POI patients and healthy controls were examined. Human ovarian granulosa-like tumor cells (KGN) underwent serum starvation (SS) treatment to induce POI cell models and then received MT treatment. The expression levels of miR-15a-5p, Stat3, p-PI3K/PI3K, p-Akt/Akt, and p-mTOR/mTOR in KGN cells were tested via quantitative real-time polymerase chain reaction and Western blotting. KGN cell viability was assessed by MTT assay and the protein levels of autophagy-related markers Beclin-1, microtubule-associated protein light chain 3 II/I, and p62 were detected by Western blotting. The binding relation between miR-15a-5p and Stat3 was verified via the dual-luciferase reporter gene assay. Functional rescue experiments were performed to probe the underlying role of miR-15a-5p/Stat3/the PI3K-Akt-mTOR pathway in KGN cell autophagy. Results miR-15a-5p was increased whilst Stat3 was decreased in the serum of POI patients and SS-induced KGN cells. MT inhibited miR-15a-5p and Stat3, activated the PI3K-Akt-mTOR pathway, and repressed cell autophagy in SS-induced KGN cells. miR-15a-5p targeted and repressed Stat3 expression. Upregulation of miR-15a-5p or downregulation of Stat3 or the PI3K-Akt-mTOR pathway promoted KGN cell autophagy. Conclusion MT suppressed miR-15a-5p and activated Stat3 and the PI3K-Akt-mTOR pathway, finally impeding SS-induced autophagy of GCs.